Identification of Two DNMT3A Mutations Compromising Protein Stability and Methylation Capacity in Acute Myeloid Leukemia. (30th October 2019) - Bruno, Samantha; Bochicchio, Maria Teresa; Franchini, Eugenia; Padella, Antonella; Marconi, Giovanni; Ghelli Luserna di Rorà, Andrea; Venturi, Claudia; Raffini, Maddalena; Prisinzano, Giovanna; Ferrari, Anna; Bandini, Lorenza; Robustelli, Valentina; et al.
Abstract : Somatic mutations of DNMT3A occur in about 20% of acute myeloid leukemia (AML) patients. They mostly consist in heterozygous missense mutations targeting a hotspot site at R882 codon, which exhibit a dominant negative effect and are associated with high myeloblast count, advanced age, and poor prognosis. Other types of mutations such as truncations, insertions, or single-nucleotide deletion also affect the DNMT3A gene, though with lower frequency. The present study aimed to characterize two DNMT3A gene mutations identified by next-generation sequencing (NGS), through analysis of protein stability and DNA methylation status at CpG islands. The first mutation was a single-nucleotide variant of DNMT3A at exon 20 causing a premature STOP codon (c.2385G > A; p.Trp795 ∗ ; NM_022552.4). The DNMT3A mutation load increased from 4.5% to 38.2% during guadecitabine treatment, with a dominant negative effect on CpG methylation and on protein expression. The second mutation was a novel insertion of 35 nucleotides in exon 22 of DNMT3A (NM_022552.4) that introduced a STOP codon too, after the amino acid Glu863 caused by a frameshift insertion (c.2586_2587insTCATGAATGAGAAAGAGGACATCTTATGGTGCACT; p. Thr862_Glu863fsins). The mutation, which was associated with reduced DNMT3A expression and CpG methylation, persisted at relapse with minor changes in the methylation profile and at protein level. Our data highlight the need to better understand the consequences of DNMT3A mutations other than R882 substitutions in the leukemogenic process in order to tailor patient treatments, thus avoiding therapeutic resistance and disease relapse.